Implementasi Multi User Operating System (OS) Dengan CCBOOT - Dio Prima Mulya; Sularno larno; Muhammad Razi (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2020)
The development of hardware and software technology has caused cybercafe and computer labs to raise the level of the operating system installed on their hardware. The Windows 7 operating system that is usually paired with PC devices is not compatible because there is no software update available for the Windows 7 version. At present, the operating system used is WINDOWS 10, but businesses have difficulty implementing or installing WINDOWS 10 on the device. they. One application that is used to facilitate the use of WINDOWS 10 is CCBoot. This research was conducted by directly applying the use of WINDOWS 10 on a Personal Computer (PC) device with an additional CCboot application. From the results of this study will be concluded whether the implementation of a diskless system with CCBoot can optimize the use of hardware.